2006
DOI: 10.1063/1.2159492
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic characterization of the ground and low-lying electronic states of Ga2N via anion photoelectron spectroscopy

Abstract: Anion photoelectron spectra of Ga(2)N(-) were measured at photodetachment wavelengths of 416 nm(2.978 eV), 355 nm(3.493 eV), and 266 nm(4.661 eV). Both field-free time-of-flight and velocity-map imaging methods were used to collect the data. The field-free time-of-flight data provided better resolution of the features, while the velocity-map-imaging data provided more accurate anisotropy parameters for the peaks. Transitions from the ground electronic state of the anion to two electronic states of the neutral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 45 publications
(41 reference statements)
5
23
0
Order By: Relevance
“…The appearance of bands X and A is similar to analogous bands seen in the Ga 2 N -PE spectrum. 6 Assignment of these bands is discussed in section IV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The appearance of bands X and A is similar to analogous bands seen in the Ga 2 N -PE spectrum. 6 Assignment of these bands is discussed in section IV.…”
Section: Resultsmentioning
confidence: 99%
“…In this article, we describe the findings for the ground and lowlying electronic states of the Al 2 N molecule using negative ion photoelectron (PE) spectroscopy and compare the results with the isovalent B 2 N and Ga 2 N molecules. 5,6 This investigation represents our continued effort to characterize group III-V molecular clusters [7][8][9][10][11][12][13] by anion PE spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…This pulsed ion beam instrumentation is based on work by Johnson and Lineberger, 26 with various configurations implemented in our group over the years. [34][35][36][37] Anion PE spectroscopy has been shown to be an extremely versatile technique, since it maps out the electronic and vibrational structures of any neutral species that can be accessed by photodetachment of a negative ion. Somewhat poorer resolution but much higher collection efficiency is achieved using "magnetic bottle" analyzers.…”
Section: Transition State Spectroscopy "Tss… Via Negative Ion Phomentioning
confidence: 99%
“…Himmel and Hebben [4] have performed matrixisolation experiments to study the interaction between Ga atoms and N 2 by using Raman and UV/Vis spectroscopies for detection and analysis. Very recently, Sheehan et al [5] have presented the spectroscopic characterization of the ground and low-lying electronic states of Ga 2 N via anion photoelectron spectroscopy. On the theoretical front, some research works have been reported with particular emphasis on the stoichiometric clusters (Ga n N n , n = 1-12) [6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%